Pomeron/glueball and odderon/oddball trajectories - Szanyi, István; Jenkovszky, László; Schicker, Rainer; Svintozelskyi, Volodymyr (Nuclear physics. A, Nuclear and hadronic physics, 2020)
We predict glueball/oddball resonances lying on the pomeron/odderon trajectories. A simple new form of the trajectories, with threshold and asymptotic behaviour required by analyticity and unitarity, is proposed. The parameters of these (pomeron and odderon) trajectories are fitted to the data on high-energy elastic proton-proton and proton-antiproton scattering. The fitted trajectories are extrapolated to the resonance region to predict masses and widths of glueballs and oddballs. The (pomeron and odderon) trajectories may be used to calculate processes of central exclusive diffraction (CED).
Gesehen am 12.05.2020